2011
DOI: 10.1038/ejhg.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

The potential influence of KIR cluster profiles on disease patterns of Canadian Aboriginals and other indigenous peoples of the Americas

Abstract: Genetic differences in immune regulators influence disease resistance and susceptibility patterns. There are major health discrepancies in immune-mediated diseases between Caucasians and Canadian Aboriginal people, as well as with other indigenous people of the Americas. Environmental factors offer a limited explanation as Aboriginal people also demonstrate a rare resistance to chronic hepatitis C virus infection. Killer immunoglobulin-like receptors (KIRs) are known modulators of viral responses and autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
(64 reference statements)
4
22
1
Order By: Relevance
“…Genetic studies by our lab and others indicate that Manitoban FN and Métis populations have a reduced genetic tendency to produce IL-10 compared to non-Aboriginals [70,71]. Moreover, we found that PBMC from virally-naïve FN individuals produced significantly less IL-10 in response to HCV core protein than cells isolated from non-FN individuals, suggesting that FN cells were not as susceptible to immune deregulation upon first encounter with the virus [70,72]. …”
Section: Rates Of Chronicitymentioning
confidence: 72%
See 2 more Smart Citations
“…Genetic studies by our lab and others indicate that Manitoban FN and Métis populations have a reduced genetic tendency to produce IL-10 compared to non-Aboriginals [70,71]. Moreover, we found that PBMC from virally-naïve FN individuals produced significantly less IL-10 in response to HCV core protein than cells isolated from non-FN individuals, suggesting that FN cells were not as susceptible to immune deregulation upon first encounter with the virus [70,72]. …”
Section: Rates Of Chronicitymentioning
confidence: 72%
“…The disparities in KIR gene profiles of virally naïve Aboriginals as compared to non-Aboriginals paralleled these disparities reported for better as compared to worse outcomes for HCV infection, suggesting the further involvement of biological processes in racial trends of HCV chronicity [72]. Coincidently, the unique KIR gene profile and genotypes of Manitoban Aboriginals were similar to other KIR analyses performed within indigenous peoples throughout the Americas; whereas, data from Manitoban Caucasians reflected that of Caucasian globally [72]. This might be accounted for by a common ancestry or an abrupt immune selection such as the “old world” disease epidemics that swept through indigenous communities [75,76,77,78].…”
Section: Rates Of Chronicitymentioning
confidence: 97%
See 1 more Smart Citation
“…[131]. Recent studies suggest unique host immunity may enhance spontaneous clearance of HCV in certain Aboriginal populations [137][138]. One study compared…”
Section: Discussionmentioning
confidence: 99%
“…Because KIR3DS1, 2DS1, and 2DS5, as well as 2DL5A, are linked together as the T4 cluster at the telomeric half of the KIR gene complex, we compared the carrier frequency of individuals carrying this gene cluster between the northern and southern Persian populations and observed a significant increase of T4 gene clusters in northern Persians compared with southern Persians (p ϭ 0.03; Table 2). Further comparison with world populations reveals that the T4 gene cluster occurs at high frequencies in Amerindian populations, such as Yucpa (74%), Amazonian (67.5%), Tarahumara (66.1%), Canadian Aboriginal (65.3%), and Purepecha (62.2%), as well as in southern Indian populations (60%) [20,23,29,30].…”
Section: Resultsmentioning
confidence: 99%